Thinking the Revolution in Alberto Seixas Santos’s Mild Manners and Gestures and Fragments - Trindade, Luís (Cinema: Journal of Philosophy and the Moving Image, 2014)
This article analyses the ways in which two films by Portuguese filmmaker Alberto Seixas Santos, Mild Manners (Brandos Costumes, 1974) and Gestures and Fragments (Gestos e Fragmentos, 1982), engage with history and, in particular, with the Carnation Revolution of 1974-1975. The article argues that the director’s politics should be looked for in the ways both films participate in the general critique of audiovisual forms of the 1960s and the 1970s, rather than in specific ideological positions conveyed in the narratives. In this context, Mild Manners and Gestures and Fragments deploy forms of philosophical thought to mediate the relation between their narratives and the revolutionary process. More specifically, whereas The Commu- nist Manifesto of Marx and Engels provide the former with a utopian impulse, the considerations of Portuguese philosopher Eduardo Lourenço about the Carnation Revolution in Gestures and Fragments is instrumental in the definition of this second film as a reflection on the revolution’s memory. In both cases, by rigorously equating representation and thought, Seixas Santos’s films are allowed to emerge as faithful figurations of a particularly critical historical moment.